Disaster Management of Pandemic COVID-19 toward Tourism of Bintan Regency by NVivo Analysis - Mahadiansar, Mahadiansar; Pratiwi, Mirza Ayunda; Putri, Rizqi Apriani; Valentina, Annissa (Universitas Muhammadiyah Yogyakarta, 2023)
Bintan Regency has a strategic location close to Singapore (it only takes 60 minutes by ferryboat). Therefore, tourism is one of the primary sectors contributing to the highest local government revenue of the Bintan Regency. During the COVID-19 pandemic, all the entrances from abroad were closed. Then it finally decreased to 94% of the local government revenue. The Ministry of Tourism and Creative Economy has recommended the